Global to regional scale evaluation of adaptation measures to reduce the future water gap. (February 2020) - Straatsma, Menno; Droogers, Peter; Hunink, Johannes; Berendrecht, Wilbert; Buitink, Joost; Buytaert, Wouter; Karssenberg, Derek; Schmitz, Oliver; Sutanudjaja, Edwin H.; van Beek, L.P.H.; Vitolo, Claudia; Bierkens, Marc F.P.
Abstract: The global water gap, water demand minus water supply, is expected to increase through 2100, negatively affecting agriculture, industry and households. Adaptation measures are necessary, but projections on their effectiveness and costs are currently unavailable. Here, we present an adaptation evaluation framework aimed at closing the water gap, which is applied offline at the global scale, and made available for regional decision making as a web service. It includes climate change and socioeconomic scenarios over the 21st century as drivers for global projections of water supply and demand. The transient water gap was calculated for 1604 water provinces globally and we determined the water gap reduction that could be achieved by three increasingly involved sets of adaptation measures. The median annual adaptation costs amount to 1.4–1.6% of the GDP per affected water province. The interactive web-based simulation allows users to include information that is not available at the global scale. Highlights: A framework combining global and regional scale projections of water gap reductions. Distinct temporal differences between the trajectories of the global water gap after 2045. No full water gap closure when minimum river flows are maintained. Costs of measures are of the same magnitude as the costs of major natural disasters. Web-based interaction enables inclusion of detail unavailable at the global scale.